Sistem Pendukung Keputusan Menggunakan WASPAS dalam Menentukan Rumah Kost yang Strategis - Elisabet Yunaeti Anggraeni; Adi Prasetia Nanda; Nungsiyati Nungsiyati (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
A boarding house is a place to stay temporarily when you have to be away from your house or the area where you live. In Indonesia, there are many students who, after graduating from high school or the equivalent, continue their studies outside the city, some even outside the province or island. The choice to continue their studies outside the area is based on several reasons, including because the majors desired and in accordance with their interests and talents are not available in their area of origin. Therefore, leaving the area or city of birth and settling in the area or city where the desired university is located must be an option. The development of a campus or college has an impact on the increasing demand for property by consumers, especially the need for boarding houses. Based on this background, it is necessary to determine strategic boarding houses using the Waspas method. The results of the calculations in determining strategic boarding houses are: 1. Melati boarding house (Q3) 8,700, 2. Anyelir boarding house (Q1) 6,342, 3. Orchid boarding house (Q4) 5,688, 4. Mawar boarding house (Q2) 5,502 . 5. Akasia boarding house (Q5) 5,125.